Nikuñja : Gvāliyara Rājya ke vartamāna kavi-hrdaya - Kiśora, Rāmakiśora Śarmā, 1903- (SAMP early 20th-century Indian books project, 1932)
Anthology of Hindi poems written by poets belonging to the erstwhile Gwalior Princely state.